Impact of Spin Slip Conditions on the Axisymmetric Rotation of a Spherical Particle in a Couple Stress Fluid Within a Cavity - NISHAD, Shekhar; MADASU, Krishna Prasad (Engineering Transactions, 2025)
This paper investigates the effect of spin slip condition on the flow of a couple stress fluid between two concentric spheres. The spherical particles rotate about the z-axis with different angular velocities  and  under the assumption of low Reynolds numbers. To solve the governing equations, we impose tangential slip and couple stress spin slip boundary conditions at the surfaces of the particle and the cavity wall. The nondimensional torque is computed, tabulated and graphically analyzed for various values of the separation parameter, couple stress viscosity, angular velocity ratio, tangential slip, and couple stress spin slip parameters. Our findings indicate that torque value increases with higher values of the couple stress viscosity parameter, separation parameter, tangential slip parameter, and spin slip parameter. However, the torque decreases as the angular velocity ratio increases. Furthermore, our results agree with previously published findings for cases with vanishing tangential slip and spin slip at the particle and cavity surfaces.